Climate change and migration: Exploring the role of environmental factors in migration decision-making in Nepal and Bangladesh - Bautdinova, Iuliia (2022)
As climate change is reshaping our world, millions are expected to respond to its impacts by moving in the coming decades. While climate change-induced events do undermine the security and stability of livelihoods, there is little empirical and theoretical evidence that climate change is the sole or main driver of migration. As the nature of migration decision-making is incredibly complex and influenced by multiple drivers, including individual characteristics of the households, it is important to understand how environmental change interacts with economic, social and political drivers of migration, how migrants perceive environmental changes, and under what circumstances migration eventually takes place. Based on semi-structured interviews with twenty-four migrants from Nepal and Bangladesh, both international and internal, this study unveils how these migrants’ perceptions of environmental change shape their decision to migrate. I found that the relationship between environmental change and migration decision-making is not linear and is interconnected with economic, social, and political drivers that are already present in communities. Whilst the findings of this qualitative research cannot be generalized, they contribute to the growing scholarship exploring the complexity of migration decision-making where some drivers are seen as dominating, interconnecting, or exacerbating others (the minimalist school). Further research in the field could help analyze dynamics in environmentally vulnerable communities and support policies that facilitate safe and regular migration.